Can body traits, other than wings, reflect the flight ability of Triatominae bugs? - Hernández, María Laura (2015)
Triatominae insects are vectors for Trypanosoma cruzi, the Chagas disease parasite, and their flying behaviour has epidemiological importance. In Triatominae, the flying capacity shows striking differences among species, but also within species between sexes or individuals. In Triatoma infestans, it has been shown that an important proportion of individuals could have wings but no flying muscles. In other species, no clear relationships could be observed between wing lenght and flying behaviour. If wing presence or size is not a warrant of the flying behaviour, which other parts of the body could be taken as a reliable witness of this important function?